Effect of Thermomechanical Treatment on Subsequent Deformation Behavior in a Binary Z1 Magnesium Alloy Studied by the Acoustic Emission Technique. Issue 3 (27th December 2018) - Drozdenko, Daria; Bohlen, Jan; Horváth, Klaudia; Yi, Sangbong; Letzig, Dietmar; Chmelík, František; Dobroň, Patrik
Abstract : Pre‐straining of magnesium alloy modifies the final texture of the material and therefore leads to a different deformation behavior during subsequent loading. At the same time, heat treatment in the context of thermo‐mechanical procedures is used as softening mechanism, as well as for age hardening processing. In mechanical conditions with twin‐dominated deformation in textured magnesium alloys, the twin boundaries can be pinned if existing after a pre‐deformation of samples and therefore influence their mobility. The impact of the ongoing mechanical behavior is discussed. In the present paper, a procedure of pre‐compression and reverse tensile loading of extruded binary magnesium alloy Mg–1 wt% Zn (Z1) is used and intermediate aging at 200 °C is applied in two different routes. The effect of the heat treatment on the flow behavior during subsequent mechanical loading is correlated with the dominating deformation mechanisms revealed by in situ acoustic emission measurements and ex situ scanning electron microscopy. The pinning of twin boundaries can restrict their mobility in experimental environments that favor the recovery of the samples. As a result, new twins easily nucleate if the concurrent re‐orientation of the lattice is favorable for strain accommodation. Abstract : The effect of pre‐compression and concurrent activation of slip and twinning as well asintermediate isothermal aging on the mechanical response during subsequent tensile loading iselucidated by acoustic emission technique . Detwinning can proceed by migration ofpinned twin boundary and by activation of new twins inside existing twin lamellae.